2015
DOI: 10.1002/jms.3520
|View full text |Cite
|
Sign up to set email alerts
|

Structure and further fragmentation of significant [a3 + Na − H]+ions from sodium-cationized peptides

Abstract: A good understanding of gas-phase fragmentation chemistry of peptides is important for accurate protein identification. Additional product ions obtained by sodiated peptides can provide useful sequence information supplementary to protonated peptides and improve protein identification. In this work, we first demonstrate that the sodiated a3 ions are abundant in the tandem mass spectra of sodium-cationized peptides although observations of a3 ions have rarely been reported in protonated peptides. Quantum chemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
(143 reference statements)
0
3
0
Order By: Relevance
“…The coordinates from the crystal structure of 2 were used as a starting point for our computational analysis. We carried out molecular dynamic (MD) simulations using the Discovery Studio (DS) 2.5 program package and the method settings described in a previous work 34 to provide stable structures for compound 2 in the gas-phase. At completed simulation, the 10 most stable structures were selected and further optimized in Gaussian 09 to refine the previous result and find the lowest energy structure.…”
Section: Dft Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coordinates from the crystal structure of 2 were used as a starting point for our computational analysis. We carried out molecular dynamic (MD) simulations using the Discovery Studio (DS) 2.5 program package and the method settings described in a previous work 34 to provide stable structures for compound 2 in the gas-phase. At completed simulation, the 10 most stable structures were selected and further optimized in Gaussian 09 to refine the previous result and find the lowest energy structure.…”
Section: Dft Calculationsmentioning
confidence: 99%
“…The coordinates of the crystal structure of olefin-imidacloprid were analysed using the Discovery Studio (DS) 2.5 program package as described in a previous paper. 34 100 different conformers were obtained and the 10 most stable candidate structures were selected and reoptimized using DFT calculations implemented in the Gaussian 09 suite of programs to find the lowest energy state. The most favourable conformer resembled the crystal structure of compound 2 with the nitrogen N(5) of the pyridine group facing the opposite direction of the nitroguanidinyl group (this difference can be reasonably accommodated by favourable packing forces in the crystal structure of 2, Fig.…”
Section: Density Functional Calculations On the Fragmentation Of 2h +mentioning
confidence: 99%
“…It has been demonstrated that sodiated peptides often undergo fragmentation pathways that differ from those of protonated peptides; thus they would provide complementary peptide sequencing information. Our previous studies indicated that peptides accommodate Na + by the available carbonyl O and amino N atoms to disperse the charge, thus bending the peptide to generate special fragmentation. Thus, sodiated peptides fragment in a somewhat “charge‐remote” way (that charge is fixed in a local area and dissociation is not always initiated by the flow of a charge carrier) .…”
mentioning
confidence: 99%